The Effectiveness of Google Earth as a Geography Learning Medium on High School Students' Spatial Thinking Skills: A Systematic Literature Review - M Rizqon Al Musafiri; Ahmad Irfan Ilhami (Divisi Penelitian Yayasan Simfoni Ilmu Cendekia, 2026)
Spatial thinking ability is an essential competency in geography learning that demands optimal use of technology-based media. This study aims to systematically analyze the effectiveness of Google Earth as a geography learning medium on the spatial thinking ability of senior high school students. The method used is Systematic Literature Review (SLR) following the PRISMA protocol. Literature searches were conducted through Google Scholar, ERIC, and Scopus databases using predetermined keywords, covering publications from 2015 to 2024. Of 187 identified articles, 24 met the inclusion criteria and were thoroughly analyzed. Results indicate that: (1) Google Earth consistently improves students' spatial thinking ability with an average increase of 23.4% compared to conventional learning; (2) the highest effectiveness was found in topography, distribution pattern analysis, and image interpretation; (3) integrating Google Earth with Problem-Based Learning and Project-Based Learning models yielded more significant impacts. These findings have important implications for geography teachers and curriculum developers in designing geospatial technology-based learning.